2019
DOI: 10.1002/csr.1726
|View full text |Cite
|
Sign up to set email alerts
|

The influence of financial performance on corporate social innovation

Abstract: The study draws from the literature on corporate social innovation (CSI) and financial performance and extends previous studies about this relationship. In addition, given the scant literature on corporate social innovation, the paper tries to generate a common framework for this topic. It proposes a definition and a measure of CSI. The measure aims to reflect the contribution that firms make to society in terms of innovation.The sample includes firm observations that cover 6-year longitudinal panel data, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 72 publications
0
11
0
2
Order By: Relevance
“…However, the last two research steams (c) and (d) identified a positive relationship. Alonso‐Martínez et al (2019) identified one‐year, lagged, positive relationship between financial performance with corporate social innovation. Setó‐Pamies (2015) identified a positive relationship between board gender diversity and CSR.…”
Section: Content Analysis and Discussion Of Clustersmentioning
confidence: 99%
“…However, the last two research steams (c) and (d) identified a positive relationship. Alonso‐Martínez et al (2019) identified one‐year, lagged, positive relationship between financial performance with corporate social innovation. Setó‐Pamies (2015) identified a positive relationship between board gender diversity and CSR.…”
Section: Content Analysis and Discussion Of Clustersmentioning
confidence: 99%
“…In the second phase (the selection of data), only the documents useful to the research framework, that is, containing pertinent information to investigate the application of the conceptual model, have been stored (Corbin & Strauss, 2008). In the third phase (the analysis of data), the data saved have been analyzed by coding into key themes coherent with our 1 With social innovations we mean the innovations contributing in new technological, environmental, and social ways to improve the quality of life for society, while also generating sustainable economic benefits (Alonso-Martínez, González-Álvarez, & Nieto, 2019;Poussing, 2019). 2 The selected case study has already been analyzed in the article of Silvestri and Veltri (2017) addressed to investigate whether an alliance guided by ethic principles could effectively conjugate ethics and business with reciprocal advantages for the organizations and the territory.…”
Section: Applying the Research Framework To A Real Case Studymentioning
confidence: 99%
“…The GOEL group case study also highlights the relevance of cooperation to introduce social innovations in a disadvantaged context, that is, innovations contributing in a new technological, environmental, and social ways to improve the quality of life for society, while also generating sustainable economic benefits (Alonso-Martínez et al, 2019;Poussing, 2019). The literature underlines that social innovations are more effective if they are undertaken within a network instead of taken in isolation by a lone social entrepreneur (Phillips, Lee, Ghobadian, O'Regan, & James, 2015).…”
Section: Considering Conclusionmentioning
confidence: 99%
“…With enacting interbank money market regulations in 1987 the Central Bank intervened in the money markets for the first time aimed at stabilizing the liquidity levels (The Banks Association of Turkey, 2005). Started from 1994, the government regulations demanded that all stock transactions started to be conducted by the means of electronic devices and computers (Aldis, 2011). The Banking Regulation and Supervision Agency (BRSA) was established to ensure stability in financial markets and coordinate the operation of financial institutions (The Banks Association of Turkey, 2005).…”
Section: Public Interest Statementmentioning
confidence: 99%